2020
DOI: 10.1017/s2040174420000616
|View full text |Cite
|
Sign up to set email alerts
|

The newborn sheep translational model for pulmonary arterial hypertension of the neonate at high altitude

Abstract: Chronic hypoxia during gestation induces greater occurrence of perinatal complications such as intrauterine growth restriction, fetal hypoxia, newborn asphyxia, and respiratory distress, among others. This condition may also cause a failure in the transition of the fetal to neonatal circulation, inducing pulmonary arterial hypertension of the neonate (PAHN), a syndrome that involves pulmonary vascular dysfunction, increased vasoconstrictor tone and pathological remodeling. As this syndrome has a relatively low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 146 publications
(268 reference statements)
0
10
0
Order By: Relevance
“…In this study, we tested whether treatment with 2-APB for 10 days can ameliorate the pulmonary arterial hypertension in hypoxic newborn lambs, conceived, gestated, born, and studied during their first 15 days of postnatal life at the Andean Altiplano at 3,600 m.a.s.l. This is a well-established model, showing increased basal mPAP and PVR, with also a greater increase in mPAP and PVR in response to acute hypoxia compared with the lowland controls (Herrera et al, 2007(Herrera et al, , 2019Lopez et al, 2016;Gonzaléz-Candia et al, 2020). Our results showed that 2-APBtreated lambs had a lower mPAP between the first and the third day of treatment and during the fifth, the sixth, and the ninth day of treatment compared with the vehicle-treated lambs (P < 0.001 for the global effect of the factor treatment in twoway ANOVA), but at the end of the treatment, mPAP did not differ between groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, we tested whether treatment with 2-APB for 10 days can ameliorate the pulmonary arterial hypertension in hypoxic newborn lambs, conceived, gestated, born, and studied during their first 15 days of postnatal life at the Andean Altiplano at 3,600 m.a.s.l. This is a well-established model, showing increased basal mPAP and PVR, with also a greater increase in mPAP and PVR in response to acute hypoxia compared with the lowland controls (Herrera et al, 2007(Herrera et al, , 2019Lopez et al, 2016;Gonzaléz-Candia et al, 2020). Our results showed that 2-APBtreated lambs had a lower mPAP between the first and the third day of treatment and during the fifth, the sixth, and the ninth day of treatment compared with the vehicle-treated lambs (P < 0.001 for the global effect of the factor treatment in twoway ANOVA), but at the end of the treatment, mPAP did not differ between groups.…”
Section: Discussionmentioning
confidence: 98%
“…Both fetal and postnatal pulmonary arteries quickly contract and develop a pathological remodeling in response to hypoxia ( Gao and Raj, 2011 ; Dunham-Snary et al, 2017 ; Hussain et al, 2017 ). Therefore, the high-altitude chronic hypoxia during pregnancy and early after birth results in pulmonary hypertension of the newborn and associated cardiopulmonary risk later in life ( Herrera et al, 2015 ; Gonzaléz-Candia et al, 2020 ). We have previously established two ovine models of neonatal pulmonary hypertension induced by high-altitude hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that pregnant ewes and fetal sheep at 3600 m are hypoxemic relative to lowland animals [ 45 ]. This condition induces a marked endothelial dysfunction and vascular remodeling in the neonatal lamb which results in PAHN [ 35 , 38 , 39 , 44 ]. Furthermore, we have shown that melatonin treatment for one week improves cardiopulmonary function and structure [ 39 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…We consider that the capacity of an antenatal melatonin treatment to modulate postnatal cardiac oxidative balance is a remarkable finding, as oxidative stress is a hallmark of myocardial pathophysiology. In addition, the results are shown in a translational animal model that represents perinatal conditions in humans [ 35 , 36 ]. Therefore, our findings support melatonin as a plausible treatment in neonatal diseases that coexist with hypoxia and oxidative stress, with human translational potential to protect babies against cardiac disease induced by developmental chronic hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation